2006
DOI: 10.1007/s10764-005-9006-z
|View full text |Cite
|
Sign up to set email alerts
|

Male Mate Choice in Lemur catta

Abstract: Though females are generally more selective in mate choice, males may also derive reproductive benefits from exercising mate selectivity if one or more factors limit male reproductive success and females differ in reproductive potential. I used male mating effort as a proxy for male mate choice in ringtailed lemurs (Lemur catta). I calculated mating effort as the rate of malemale agonism during each female's estrous period 30 min before and 30 min after the first and last mountings with intromission. I collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 73 publications
(106 reference statements)
2
50
0
Order By: Relevance
“…SCI affords the opportunity to follow radio-collared individuals in a closed population in which lemurs are allowed to transfer between groups unimpeded by human intervention. Previous work has shown that L. catta on SCI exhibit species-typical social and reproductive behaviors [KeithLucas et al, 1999;Parga, 2003Parga, , 2006aParga and Lessnau, 2008]. SCI is approximately 16 km long and 3 km wide, and the L. catta groups at this location inhabit the north end of the island [Keith-Lucas et al, 1999].…”
Section: Study Site and Study Animalsmentioning
confidence: 86%
See 1 more Smart Citation
“…SCI affords the opportunity to follow radio-collared individuals in a closed population in which lemurs are allowed to transfer between groups unimpeded by human intervention. Previous work has shown that L. catta on SCI exhibit species-typical social and reproductive behaviors [KeithLucas et al, 1999;Parga, 2003Parga, , 2006aParga and Lessnau, 2008]. SCI is approximately 16 km long and 3 km wide, and the L. catta groups at this location inhabit the north end of the island [Keith-Lucas et al, 1999].…”
Section: Study Site and Study Animalsmentioning
confidence: 86%
“…The focal sampling order was randomized, with no more than 2 samples collected per individual per day to yield equal numbers of focal samples collected per individual per group in each year. During focal samples, the following agonistic behaviors were recorded to establish male dominance rankings: approach-withdraw, bite, chase, cuff, fight, grapple, lunge, nose push, push, stink fight, and take food [Jolly, 1966;Petter and Charles-Dominique, 1979;Taylor, 1986;Gould, 1994;Pereira and Kappeler, 1997;Parga, 2006a]. Ad libitum data were collected at all times.…”
Section: Data Collectionmentioning
confidence: 99%
“…Although this vocalization is used by ring-tailed lemurs of both sexes and all ages [Jolly, 1966;Macedonia, 1990Macedonia, , 1993, my study will concentrate on adult male use of purring, since anecdotal reports [Jolly, 1966] as well as my preliminary data collection on adult females provide evidence for male purring only in agonistic contexts. Additionally, a strong precedent exists for male-focused behavioural studies to be undertaken in this species [Gould, 1994[Gould, , 1997[Gould, , 2006Gould and Overdorff, 2002;Gould et al, 2003Gould et al, , 2005Parga, 2006a;Gould and Ziegler, 2007], and my study will add to this rich literature on male behaviours.…”
Section: Introductionmentioning
confidence: 93%
“…cuff, bite or jump fight). An agonistic interaction involves 1 or more acts of avoidance, aggression or defence between 2 individuals [Gould, 1994;Pereira and Kappeler, 1997;Parga 2006aParga , 2009. Times with male-male agonism were defined as 2.5-min one-zero sampling intervals that contained at least 1 instance of intrasexual agonism involving the focal male, while times without male-male agonism meant a 2.5-min sampling interval that did not contain any instances of male-male agonism involving the focal male.…”
Section: Description Of Study Animalsmentioning
confidence: 99%
“…Indeed, dominance relationships can remain stable during mating contexts, as in the tufted capuchin monkey (Cebus apella), where copulating alpha males are not interrupted by subordinate males (Janson, 1984;Lynch Alfaro, 2005). However, established male dominance relationships do not always remain stable throughout periods of female sexual receptivity in other primates.In the ring-tailed lemur (Lemur catta), females only mate during their periovulatory period (also known as vaginal estrus: Evans and Goy, 1968;Van Horn and Resko, 1977), which usually lasts for less than a day (Jolly, 1966;Evans and Goy, 1968;Van Horn and Resko, 1977;Koyama, 1988;Sauther, 1991;Parga, 2006a). In this species, males do not form coalitions (e.g., chimpanzees, Pan troglodytes: Watts, 1998) with other males when competing over access to females; instead, malemale aggression occurs between dyads (Jolly, 1966;Koyama, 1988;Sauther, 1991).…”
mentioning
confidence: 99%